Proposal of a didactic resource for the interpretation of the landscape. The field trips in the old Villena Lagoon (Alicante) - Álvaro-Francisco Morote Seguido; María Hernández Hernández (Didáctica Geográfica)
This study aims to propose the old Villena Lake (Alicante, Spain) as a teaching resource for the interpretation and analysis of the landscape. Methodologically, the materials, steps, activities and evaluation that are carried out before and during this experience have been exposed. As a conclusion, it is worth mentioning that this resource is an excellent didactic example because it allows to the students understand the complexity of the natural environment-society relationship and its manifestation through the landscape. And also, on the other hand, the meaning and value that the society assign to a certain landscape over time.